Cholesterol-Loaded Cyclodextrin Addition to Skim Milk-Based Extender Enhances Donkey Semen Cooling and Fertility in Horse Mares - Segabinazzi, Lorenzo Garrido Teixeira M. [UNESP]; Scheeren, Veronica Flores da Cunha [UNESP]; Freitas-Dell'Aqua, Camila de Paula [UNESP]; Papa, Frederico Ozanam [UNESP]; Alvarenga, Marco Antonio [UNESP]; Dell'Aqua, José Antônio [UNESP]; Canisso, Igor Frederico [UNESP] (Elsevier, 2021)
The present study aimed to compare semen parameters and fertility of cooled donkey semen extended in a commercially available skim milk (SKM) based extender and the same extender with cholesterol-loaded cyclodextrin (SKM-CLC). In Experiment 1, thirty-five ejaculates from seven jacks were split in SKM and SKM-CLC, extended at 50 million sperm/mL and stored at 5°C for 48 hours. Total motility (TM), progressive motility (PM), percentage of sperm with rapid motility (RAP) were assessed with CASA. Plasma membrane stability (PMS), and high mitochondrial membrane potential (HMP) were assessed with the combination of Yo-Pro and MitoStatusRed with flow cytometry. Semen was assessed before (0), 24 and 48h after cooling. In Experiment 2, two estrous cycles of 15 mares were used for fertility assessment. Mares were examined every other day by transrectal ultrasonography and had ovulation induced with 250 µg of histrelin acetate when a ≥35 mm follicle was first detected. Mares were randomly inseminated with semen obtained from one jack. Semen was extended in either SKM or SKM-CLC and cooled-stored for 24 hours. Pregnancy diagnosis was carried out 15-day post-ovulation. Data were analyzed with a mix model and Tukey's as posthoc and logistic regression model. Significance was set at P ≤ .05. There were no differences in TM, PM, RAP, PMS, and HMP for semen extended in either extender immediately before cooling (P > .05). There was a reduction in TM, PM, RAP, PMS, and HMP overtime across groups (P < .05); however, semen extended with SKM-CLC had superior TM, PM, RAP, PMS, and HMP than semen extended in SKM at 24- and 48-hours post-cooling (P < .05). Mares bred with semen extended in SKM had a lower conception rate (13%, 2/15 cycles) than cycles bred with SKM-CLC (47%, 7/15 cycles; P < .05). In conclusion, incorporating CLC into SKM extender improved cooling ability and fertility of donkey semen in horse mares. It remains to be determined if similar results can be obtained in clinical practice with mares and jennies.
Keywords: Cholesterol; Cryopreservation; Equus asinus; Extenders; Reproduction; Stallion